Addressing Food and Nutrition Security in Developed Countries - Pollard, Christina (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Addressing Food and Nutrition Security in Developed Countries Special Issue is a collection of papers from researchers in counties with developed economies who are responding to increasing prevalence of food insecurity. Food insecurity is relatively hidden, and the real extent of the problem is likely to be underestimated in many of these countries. Novel methods to estimate the prevalence of food insecurity in the face of no routine measurement are presented. Population surveys highlight adverse mental health outcomes and new and emerging subgroups that are experiencing food insecurity. Understanding the factors associated with food insecurity and how people cope is extremely important when considering how best to address the problem. Readers can become familiar with the lived experience of food insecurity in some countries-essential intelligence for effective policy and interventions. The extent of food banking operations and the nature of the charitable response in some countries is also described. Country-specific research highlights the importance of understanding the cultural and external environmental context. The influence the cost of food and budgetary tools on diet and food insecurity suggests opportunities for intervention. Researchers calls for social protection and high-quality dignified responses to address this complex public health problem.